Antitumour drugs targeting tau R3 VQIVYK and Cys322 prevent seeding of endogenous tau aggregates by exogenous seeds - Annadurai, Narendran; Malina, Lukáš; Salmona, Mario; Diomede, Luisa; Bastone, Antonio; Cagnotto, Alfredo; Romeo, Margherita; Šrejber, Martin; Berka, Karel; Otyepka, Michal; Hajdúch, Marián; Das, Viswanath (The FEBS journal, 2022)
Emerging experimental evidence suggests tau pathology spreads between neuroanatomically connected brain regions in a prion-like manner in Alzheimer's disease (AD). Tau seeding, the ability of prion-like tau to recruit and misfold naïve tau to generate new seeds, is detected early in human AD brains before the development of major tau pathology. Many antitumour drugs have been reported to confer protection against neurodegeneration, supporting the repurposing of approved and experimental or investigational oncology drugs for AD therapy. In this study, we evaluated whether antitumour drugs that abrogate the generation of seed-competent aggregates of tau Repeat 3 (R3) domain peptides can prevent tau seeding and toxicity in Tau-RD P301S FRET Biosensor cells and Caenorhabditis elegans. We demonstrate that drugs that interact with the N-terminal VQIVYK or the C-terminal region housing the Cys322 prevent R3 dimerisation, abolishing the generation of prion-like R3 seeds. Preformed R3 seeds (fibrils) capped with, or R3 seeds formed in the presence of VQIVYK- or Cys322-targeting drugs have a reduced potency to cause aggregation of naïve tau in biosensor cells and protect worms from aggregate toxicity. These findings indicate that VQIVYK- or Cys322-targeting drugs may act as prophylactic agents against tau seeding.
Keywords: tau Proteins; mozek; tau seeding; proteiny tau; tau aggregation; priony; Alzheimerova nemoc; Alzheimer Disease; antitumour agents; lidé; prion-like; protinádorové látky; Alzheimer's disease; Humans; Antineoplastic Agents; Brain; Prions